Ultrasonic Assisted Flocculation of Azophloxine Using Polyaluminum Chloride - Zhang, Wenjie; Du, Ling; He, Hongbo (Asian Journal of Chemistry, 2015)
A combination of flocculation with polyaluminum chloride and ultrasonic treatment was explored in decoloration of azophloxine. The solely using of ultrasonic treatment cannot decolorize the dye efficiently. The decoloration efficiency reaches the maximum value of 72.4 % at polyaluminum chloride amount of 12 mg/L when using polyaluminum chloride alone. Twenty minutes of flocculation is considered to be the optimal condition. Ultrasonic treating time shows very small influence on azophloxine flocculation by polyaluminum chloride. With the variation of ultrasonic power between 40 and 90 W, decoloration of the dye increases firstly and then decreases. The maximum decoloration rate is obtained using ultrasonic power of 50 W, at which 79.6 % of the initial azophloxine is decolorized after 0.5 h. It is interesting that decoloration rate increases with increasing initial azophloxine concentration.